Alcohol drinking cessation and the risk of laryngeal and pharyngeal cancers: a systematic review and meta-analysis. - Aliasghar Ahmad Kiadaliri; Johan Jarl; Georgios Gavriilidis; Ulf-G Gerdtham (PLoS ONE)
Objective To evaluate the effect of alcohol cessation on the risk of developing laryngeal and pharyngeal cancers, combining available evidence in the scientific literature in a meta-analysis. Methods A systematic literature review was conducted, and a meta-analysis was applied on the retrieved studies. The generalised least squares method was used to estimate the trend from dose-response data to assess changes in the risks of laryngeal and pharyngeal cancers after drinking cessation. Results A total of 9 case-control studies were included in the meta-analysis (4 and 8 estimates for laryngeal and pharyngeal cancers, respectively). On average, alcohol drinking cessation was associated with a 2% yearly reduction in the risk of developing laryngeal and pharyngeal cancers. There was a considerable heterogeneity between the studies of pharyngeal cancer, but this was mostly due to two studies. The increased risk of laryngeal and pharyngeal cancers caused by alcohol was reversible; the time periods until the risks became equal to those of never drinkers were 36 (95% CI 11-106) and 39 (95% CI 13-103) years, respectively. Moreover, 5 years of drinking cessation was associated with a reduction of around 15% in the alcohol-related elevated risk of laryngeal and pharyngeal cancers. Conclusion Although a long time period is required to completely eliminate the alcohol-related elevated risk of laryngeal and pharyngeal cancers, a substantial risk reduction can be seen in the short term (5-10 years), and drinking cessation should therefore be encouraged to reduce the incidence of these cancers.